Support in digital health skill development for vulnerable groups in a public library setting: perspectives of trainers - Lucille M. B. Standaar; Lucille M. B. Standaar; Lucille M. B. Standaar; Adriana M. C. Israel; Rosalie van der Vaart; Brigitta Keij; Roland D. Friele; Roland D. Friele; Mariëlle A. Beenackers; L. H. D. van Tuyl (Frontiers in Digital Health)
IntroductionThe digitalization of healthcare poses a risk of exacerbating health inequalities. Dutch public libraries offer freely accessible e-health courses given by trainers. However, there is limited knowledge on whether these libraries successfully reach and support those in need. This study aimed to explore trainers’ perspectives on the challenges, successes, and potential improvements in digital health skill education in a library setting.Materials and methodsTrainers of the e-health course were interviewed. Topics included: the role of the library in digital health skills education, the successes and challenges in reaching groups with a low socioeconomic position, the perceived impact of the digital health skills education, and strategies for future improvement in digital health skills education. A deductive analysis based upon the interview guide topics was performed. A second inductive analysis was applied to identify underlying patterns. Coding was done independently and cross-checked. Codebooks and themes were determined in discussion with authors.ResultsThree themes emerged. 1) Trainers’ services, skills and expertise: Trainers identified older adults, youth, people with low (digital) literacy, the unemployed, and people from non-native cultural backgrounds as the groups most in need of support. Trainers felt equipped to address these groups’ needs. 2) The libraries’ reach: improving engagement, perceived accessibility, and clients’ barriers: Despite trainers’ efforts to adjust the course to the target groups’ level of commitment, digital and literacy levels, and logistics, the digital health course predominantly engages older adults. Experienced barriers in reach: limited perceived accessibility of the public library and clients’ personal barriers. 3) Collaborations with healthcare, welfare and community organizations: Trainers emphasized that collaborations could enhance the diversity and number of participants. Current partnerships provided: reach to target groups, teaching locations, and referral of clients.DiscussionTrainers in public libraries recognize a various target groups that need support in digital health skill development. The study identified three challenges: accessibility of the digital health course, reach of the public library, and clients’ personal barriers. Public libraries have potential to support their target groups but need strategies to improve their engagement and reach. Collaborations with healthcare, welfare, and community organizations are essential to improve their reach to those most in need of support.